INFLUENCE OF ACTIVE SUBSTANCES ON THE EFFICIENCY OF POLYMER COMPOSITE MATERIALS IN THE FORM OF VARNISH WITH FUNGICIDAL ACTION - KACHAN, ROMAN; STRASHYI, VLADYSLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper studied the effectiveness of the fungicidal effect of the polymer composite material in the form of varnish after the introduction of fungicidal agents into the base. Fungicidal activity was determined using the agar diffusion method. The causative agents of onychomycosis were used as test microorganisms: T. mentagrophytes, A. _ niger, C. _ albicans. It was established that all variants of varnish with fungicidal agents, which were not previously used in antifungal agents, have more pronounced fungicidal properties than the control sample (known antifungal varnish). They were active against all main groups of onychomycosis pathogens. An important element of the effectiveness of antifungal varnishes is their prolonged fungicidal effect over time. Even if the varnish will have pronounced fungicidal properties, but this action will not be long-lasting, the tool will not be useful for the prevention and treatment of onychomycosis. Based on the results of the study, it was proved that the proposed variants of varnishes with a fungicidal agent (a mixture of four ammonium salts) have a prolonged fungicidal effect of at least 11 days. This is ensured by several factors: the mixture of four ammonium salts has a prolonged antimicrobial effect and the polymer composite material evenly diffuses the fungicidal agent. The work also determined another important element of the effectiveness of varnishes - the loss of the fungicidal effect of the polymer composite material due to the process of leaching of the active substance upon contact with water. It has been proven that the fungicidal agent does not wash out in significant quantities from the varnish during long-term contact with water. Thus, effective versions of varnishes with a fungicidal effect were obtained, which have a prolonged effect and the fungicidal agent is not washed away with water from this material.
Keywords: polymer composite material with fungicidal properties; varnish; fungicidal agent; prolonged fungicidal effect; mixture of four ammonium salts